Scaling Law Analysis and Aftershock Spatiotemporal Evolution of the Three Strongest Earthquakes in the Ionian Sea During the Period 2014–2019 - Kyriaki Pavlou; Georgios Michas; Filippos Vallianatos (Geosciences)
The observed scaling properties in the three aftershock sequences of the recent strong earthquakes of magnitudes Mw 6.1, Mw 6.4 and Mw 6.7, which occurred in the Ionian island region on the 26 January 2014 (onshore Cephalonia Island), 17 November 2015 (Lefkada Island) and 25 October 2018 (offshore Zakynthos Island), respectively, are presented. In the analysis, the frequency–magnitude distributions in terms of the Gutenberg–Richter scaling relationship are studied, along with the temporal evolution of the aftershock sequences, as described by the Omori–Utsu formula. The processing of interevent times distribution, based on non-extensive statistical physics, indicates a system in an anomalous equilibrium with long-range interactions and a cross over behavior from anomalous to normal statistical mechanics for greater interevent times. A discussion of this cross over behavior is given for all aftershock sequences in terms of superstatistics. Moreover, the common value of the Tsallis entropic parameter that was obtained suggests that aftershock sequences are systems with very low degrees of freedom. Finally, a scaling of the migration of the aftershock zones as a function of the logarithm of time is discussed regarding the rate strengthening rheology that governs the evolution of the afterslip process. Our results contribute to the understanding of the spatiotemporal evolution of aftershocks using a first principles approach based on non extensive statistical physics suggesting that this view could describe the process within a universal view.